(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article describes the theoretical and practical approaches of foreign scientists to the influence of psychogenetic factors on the development of twins, as well as the influence of psychogenetic factors on the socialization of twins in Uzbek families.